. . . [ellipsis] - Ernest, Alicia C., author; Broadfoot, Kirsten, advisor; Diffrient, Scott, advisor; Ishiwata, Eric, committee member (Colorado State University. Libraries, 2010)
The ellipsis performs various functions in U.S. culture. It euphemizes, it transgresses, it represents an omission of text, and it occupies a space between words and yet has meaning. For these reasons, the ellipsis is an appropriate icon to organize the chapters of this text. This thesis proposes that the speaking subject is always already in a position that is simultaneously defined and transgressed by language and analyzes the subsequent linguistic performances enacted to negotiate with that position. The borders that form individual and national identity perceptions are imagined and yet, consequential. All speaking subjects exist in a space of discontinuity and must forever negotiate the irreducible gap between meaning and language, and subsequently, a temporal experience of identity. This thesis proposes that this condition of language renders the speaking subject a linguistic audience as abject. In an effort to negotiate this unbearable abjection, the speaking subject continuously participates in identity boundary performances in order to delineate spaces of self and other and spaces of identification, as well as to experience meaning. This delineation process in itself is neutral, but must be analyzed for its effect in practice. The effects of these performances become highly consequential in the complicated and highly contested spaces of national identity. In these spaces, the illusive boundary between self and other is exaggerated with simultaneous attempts to assimilate difference within. It is the task of this thesis to engage poststructural and psychoanalytic theories with texts that inform and delineate the frames of U.S. national identity and Native American identity. This thesis will primarily take up and build upon Kristiva’s abjection, Baudrillard’s conceptions of the virtual positive, and a Barthesian and Derridian influenced notion of authority. These theories are then engaged in an analysis of texts that inform Native American realities. The purpose for this engagement will be to challenge the reader to realize her/his own authority in the texts that inform her/his own identity and the identity of the self-created other. The aim is to position the subject in a space of conscious participation in responsible meaning making. The analysis will focus on the texts, “Native” and “House Bill 10-1067,” relying on these texts’ intertextual references to complicate seemingly harmless recent associations. These texts are relevant to this study because they continue to inform past and present conceptions of the United States as a nation-state and in turn continue to frame the material realities for Native communities. Overall, this thesis unpacks the notion that all speaking subjects are participating players on the stage of a large-scale identity boundary performance. In framing the subject’s position in this elliptical space, there is a suggestion for subjects to consider their lines in this performance, for their consequences and potential, in the forever negotiation of difference/self-reference, mise-en-abime.
Ellipsis
Covers not scanned.
Keywords: Critical discourse analysis -- Social aspects -- Colorado; Group identity -- Colorado -- Cross-cultural studies; Indians of North America -- Colorado; Poststructuralism